2022
DOI: 10.1111/ejss.13313
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic changes of soil air‐filled porosity associated with soil shrinkage in a Vertisol

Abstract: Soil aeration is critical for crop growth, which is generally assessed by air-filled porosity (AFP). In non-rigid soils with high shrinkage and swelling, the AFP is not only related to the total porosity and soil moisture, but also to the soil shrinkage behaviour. However, the relationship between AFP and soil shrinkage has not been clarified. The objectives of this study were to (1) establish a mathematical equation to describe the behaviours of AFP associated with soil shrinkage (AFP sh ); and (2) to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…They further established new shear strength equations for root-soil complexes of D. linearis based on the modified Wu-Waldron model and Coulomb's formula. Based on experimental measurements, Wang, Zhang, et al (2022) established a mathematical equation capable of describing the kinetics of changing air-filled porosity (AFP) along soil shrinkage process. They further demonstrated that porosity variations during soil shrinkage are often significant and would largely bias the AFP prediction, and thereby are indeed not negligible.…”
mentioning
confidence: 99%
“…They further established new shear strength equations for root-soil complexes of D. linearis based on the modified Wu-Waldron model and Coulomb's formula. Based on experimental measurements, Wang, Zhang, et al (2022) established a mathematical equation capable of describing the kinetics of changing air-filled porosity (AFP) along soil shrinkage process. They further demonstrated that porosity variations during soil shrinkage are often significant and would largely bias the AFP prediction, and thereby are indeed not negligible.…”
mentioning
confidence: 99%